Strategies of the Yogyakarta City General Election Commission in Realizing Inclusivity for Voters with Disabilities in the Yogyakarta City Regional, Indonesia Election of 2024 - Aulia, Dila Fauziatul; Kholid, Anwar (Universitas Muhammadiyah Yogyakarta, 2025)
Local elections are an important part of the democratic process and should engage everyone in society, including people with disabilities. Many previous studies have highlighted the inclusiveness of elections for people with disabilities; however, research specifically analyzing the strategies of election organizers to ensure the participation of voters with disabilities in Yogyakarta City remains limited. Therefore, by employing descriptive qualitative methods, this research aims to analyze the strategies implemented by the KPU of Yogyakarta City to ensure inclusiveness for voters with disabilities in the 2024 Yogyakarta City Elections. This research uses primary data collected through in-depth interviews with stakeholders and participant observation during the Pilkada process. The results showed that the KPU of Yogyakarta City has implemented various inclusive strategies to involve disabled groups in the Pilkada organizing process through political education, providing physical accessibility at polling stations, and training polling officers. However, due to several factors, although the number of voters with disabilities has increased, the percentage of voting rights usage has decreased. This research has limitations due to the small number of respondents with disabilities, which makes it difficult to generalize the research results.